Can we measure Individual Risk Attitudes in a Survey? - Xiaohao Ding; Joop Hartog; Yuze Sun (Tinbergen Institute, 2010)
We combine a survey and an experiment with real pay-out among Peking University students to measure and validate individual risk attitudes. The experiment involves choosing between a cash payment and playing a lottery. The survey questions ask for the reservation price of a hypothetical lottery and self-assessment of risk attitude on a 0-10 scale. We confirm familiar findings: risk aversion dominates, women are more risk averse than men, risk aversion decreases with increasing parental income, risk attitudes are domain-specific. Correlations between survey measures and experimental measures, are in the right direction, but not very high. The survey measures are valid indicators of experimentally measured risk attitude, but with substantial noise remaining. Heterogeneity in levels and structure of risk attitude is large.
Keywords: D12; 330; risk attitude; survey question; experimental validation; Risikopräferenz; Befragung; Test; China